2018
DOI: 10.1002/cbin.10938
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses of human dental pulp stem cells in lipopolysaccharide‐induced microenvironment

Abstract: This study aimed to investigate the effect of inflammatory stimuli on dental pulp stem cells (DPSCs) by assessing their proliferation and expression of genes as well as proteins in lipopolysaccharide (LPS)-induced microenvironment (iDPSCs). DPSCs were first characterized for their mesenchymal properties prior to challenging them with a series of LPS concentrations from 12 to 72 h. Following to this, their proliferation and inflammatory based genes as well as protein expression were assessed. iDPSCs had demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…In order to evaluate in vitro inflammatory mediators secreted in damaged and inflamed pulp tissue, pulp fibroblasts have been injured and/or stimulated with Gram positive lipoteichoic acid (LTA) and/or Gram negative lipopolysaccharide (LPS). Quantification of the pro-inflammatory released mediators showed that IL-6, IL-8, IL1␣ and Tumor Necrosis Factor-␣ (TNF-␣) secretion increased in LPS-stimulated human DPSC [45]. Application of CSC has been shown to modulate pro-inflammatory mediator secretion.…”
Section: Impact Of Direct Pulp Capping On the Initial Steps Of Inflammentioning
confidence: 99%
“…In order to evaluate in vitro inflammatory mediators secreted in damaged and inflamed pulp tissue, pulp fibroblasts have been injured and/or stimulated with Gram positive lipoteichoic acid (LTA) and/or Gram negative lipopolysaccharide (LPS). Quantification of the pro-inflammatory released mediators showed that IL-6, IL-8, IL1␣ and Tumor Necrosis Factor-␣ (TNF-␣) secretion increased in LPS-stimulated human DPSC [45]. Application of CSC has been shown to modulate pro-inflammatory mediator secretion.…”
Section: Impact Of Direct Pulp Capping On the Initial Steps Of Inflammentioning
confidence: 99%
“…Caries and pulpitis are major dental diseases that result from bacterial penetration (Kim et al, ). As the main component of the bacterial membrane, lipopolysaccharide (LPS) induces defensive inflammatory responses in the pulp (Bindal et al, ). In several experiments, LPS has been used to form a model of inflammation (Lee et al, ; Ko et al, ; Lertchirakarn and Aguilar, ).…”
Section: Introductionmentioning
confidence: 99%
“…TLR-3 agonist augments immunosuppressive potential of DPSCs and dental follicle stem cells, whereas TLR-4 agonist augments immunosuppressive properties of dental follicle stem cells but inhibits those of DPSCs [181]. Different bacterial lipopolysaccharides induce production of proinflammatory mediators IL-6, IL-8 or MCP-1 in PDLSCs and DPSCs [16,[182][183][184]. TLR-2 and TLR-4 agonists fail to induce the expression of IDO-1 on protein level in PDLSC, but TLR-2 agonist enhances IFN-γ-induced IDO-1 expression [16].…”
Section: Immunomodulatory Effect Of Mscs On Different Components Of Imentioning
confidence: 99%